EFFECT OF TEMPERATURE AND PARTICLE SIZE ON THE ALKALINE EXTRACTION OF PROTEIN FROM CHICKEN BONE WASTE - Andri Cahyo Kumoro; Sofiah Sofiah; Nurul Aini; Diah Susetyo Retnowati; Catarina Sri Budiyati (Dept. of Chemical Engineering, Diponegoro University, 2010)
Chicken bone is a waste of chicken meat processing industry and restaurants that has not been used widely, even though it contains valuable organic compounds that are functionals, such as collagenous and non collagenous protein. This research was conducted to investigate the effect of temperature and particle size on the protein extraction from chicken bones using dilute sodium hydroxide solution. Controlled parameters in this study were the solvent in the form of sodium hydroxide solution, extraction time for 1 hour, pH 10.5, the ratio of chicken bone powder: solvent (1:4 w/v), and stirring speed 200 rpm. While the operating variables included the extraction temperature of 30oC, 55oC, and 80oC, and particle size of 150 and 250 μm. Experiments were carried out by heating of 300 mL of sodium hydroxide solution with pH 10.5 in a three-necked flask equipped with Leibig condenser, thermometer, mechanical agitator and sampling device to reach the desired temperature (30oC, 55oC, and 80oC). Then, a total of 75 g of chicken bone powders with desired particle size (150μm and 250μm) was introduced into the sodium hydroxide solution and the stirrer was operated at speed of 200rpm. At every 10 minutes interval, as much as 10 mL samples were withdrawn for total protein analysis using Lowry-Folin method. The experiment was terminated after 1 hour. The results show that both increase in temperature and particle size caused an increase in the amount of extracted protein. Highest concentration of protein extracted was achieved at 630.99 mg/L, when the extraction was carried out using 250mm bone particles and temperature 80oC.